Identification of mealybugs on Piper nigrum as vector of Piper yellow mottle virus (Badnavirus: Caulimoviridae) - Miftakhurohmah Miftakhurohmah; Sri Hendrastuti Hidayat; Kikin Hamzah Mutaqin; Bonny Poernomo Wahyu Soekarno; Dono Wahyuno (Universitas Lampung, 2022)
Piper yellow mottle virus (PYMoV) is the dominant virus that causes mottle disease in black pepper (Piper nigrum). Two species of mealybugs, Ferrisia virgata and Planococcus minor have been reported as vectors of PYMoV. A different species of mealybug that has never been reported before was found in black pepper. Molecular approaches including total DNA isolation of mealybug collected from the field, mealybugs identification by DNA barcode, detection of PYMoV in single mealybugs, were conducted as an approach to identify the potential of mealybugs as PYMoV vector in the field. Mealybugs were collected from black pepper plants in Cimanggu (Bogor, West Java) and Sukamulya (Sukabumi, West Java). Characters of adult females were observed for morphological identification. Molecular-based identification of the mealybugs and PYMoV involved the following procedures: total DNA isolation, DNA amplification, nucleotide sequencing and sequence analysis. Three species of mealybugs, P. minor, F. virgata and Paracoccus marginatus were confirmed by morphological and molecular identification. This is the first report for the occurrence of P. marginatus in black pepper plants. PYMoV was successfully detected from field samples of F. virgata, P. minor and P. marginatus. This finding indicates the potential of insect vectors for disease spread and distribution.